A thousand splendid suns - Hosseini, Khaled (London Bloomsbury, 2008)
Two women born a generation apart witness the destruction of their home and family in wartorn Kabul, losses incurred over the course of thirty years that test the limits of their strength and courage
2
Keywords: Arranged marriage -- Fiction; Arranged marriage; English stories; Social conditions; Afghanistan -- Social conditions -- Fiction